POSITION OF CIRCULAR LETTER OF THE SUPREME COURT AS A FOLLOW-UP FROM THE DECISION OF THE CONSTITUTIONAL COURT NUMBER 37/PUU-IX/2011 - Suparto; Zulkifli (Awang Long Law Review, 2022)
Judicial review of Law Number 13 of 2003 concerning Manpower is carried out to the Constitutional Court (MK), one of the reasons is the implementation of Article 155 paragraph (2) has the potential to create legal uncertainty, because there are multiple interpretations related to the term "not yet determined". Constitutional Court Decision No. 37/PUU-IX/2011 granted the petitioners' request, and stated that the phrase "not yet determined" is interpreted as "not yet legally binding" as a result, the wages for the process during the suspension period must be paid until the decision is final and binding. As a follow-up to the Constitutional Court's decision, the Supreme Court (MA) issued a Supreme Court Circular (SEMA) Number 3 of 2015 and one of its contents is that employers pay processing fees for 6 (six) months. This has caused controversy because the content is different from the Constitutional Court's decision. Based on the research, the results show that the Supreme Court does have the authority to issue SEMA but it should only be for the internal judiciary and its contents are not regulatory. If it is regulatory, it should be in the form of PERMA. SEMA is not included in the scope of the Legislation as regulated in Law Number 12 of 2011 concerning the Establishment of Legislation. Regarding the norm of processing wages after the Constitutional Court's Decision Number 37/PUU-IX/2011, the Supreme Court should not need to issue SEMA Number 3 of 2015 regarding processing wages paid for 6 (six) months. The Supreme Court may also not reinterpret the process wages contained in Article 155 paragraph (2) of Law Number 13 of 2003 concerning Manpower which has been decided by the Court until it has permanent legal force. Because the position of the Constitutional Court's decision is equal to the law.